Proteae: a reservoir of class 2 integrons?. (25th February 2019) - Mendes Moreira, Ana; Couvé-Deacon, Elodie; Bousquet, Pauline; Chainier, Delphine; Jové, Thomas; Ploy, Marie-Cécile; Barraud, Olivier
Abstract: Objectives: Our aim was to confirm with a large panel of clinical isolates that class 2 integrons are highly prevalent in Proteae and to analyse their genetic characteristics. Methods: Proteae ( Proteus spp., Morganella spp. and Providencia spp.) isolates were collected from clinical samples during 2013 at Limoges University Hospital, France. The presence of class 1, 2 and 3 integrons was investigated by quantitative PCR. The presence of a stop codon in the intI2 gene was determined by Sanger sequencing. The gene cassette arrays of class 2 integrons were determined by PCR-RFLP and Sanger sequencing or next-generation sequencing when needed. Results: Of the 327 Proteae collected, 103 (31.5%) harboured a class 2 integron and 45 (13.8%) a class 1 integron. No class 3 integrons were detected. One functional IntI2 integrase was detected in a Morganella morganii isolate. Six different gene cassette arrays were detected. Four had already been described in the literature: dfrA1–sat2–aadA1 (72 isolates), dfrA1–catB2–sat2–aadA1 (17), sat2–aadA1 (6) and lnu(F), dfrA1, aadA1 (1). We identified two new gene cassette arrays: (i) a new variant of the dfrA1 gene cassette (one isolate; the one with the functional IntI2); and (ii) the array dfrA1–gcu115–sat2 harbouring the new gcu115 gene cassette with two ORFs encoding proteins of unknown functions (five isolates). Conclusions: We showed a high frequency of class 2 integrons, as well as a diversity of gene cassette arrays, among Proteae. This work highlights that the Proteae tribe plays an important role as a reservoir of class 2 integrons.